Arthritis Progression on Serial MRIs Following Diagnosis of Medial Meniscal Posterior Horn Root Tear - Krych, Aaron J.; Johnson, Nick R.; Mohan, Rohith; Hevesi, Mario; Stuart, Michael J.; Littrell, Laurel A.; Collins, Mark S. (The Journal of Knee Surgery, 2018)
Medial meniscus posterior root tears (MMPRTs) are a significant source of pain and dysfunction. The purpose of this study was to evaluate changes in the medial compartment of the knee over time following the diagnosis of a MMPRT on MRI. A retrospective review of the institutional database was performed for patients with an initial MRI diagnosis of a MMPRT. Patients were included if they had a subsequent follow-up MRI on the same knee. Patients with surgical intervention, including debridement or repair, were excluded. MRIs were evaluated by two board-certified musculoskeletal radiologists. MMPRTs were defined using the LaPrade classification, and the medial compartment articular cartilage was graded using the modified Outerbridge classification. MRIs were reviewed for meniscus extrusion, subchondral bone edema, and insufficiency fractures. Patients were divided into two groups for the analysis to account for differences in MRI time intervals. Group 1 had a follow-up MRI within 12 months of initial imaging (subacute group) and Group 2 had a follow-up MRI greater than 12 months after initial imaging (chronic group). Forty-one knees and 82 MRIs were analyzed, including 20 knees/40 MRIs (13 females, 7 males) in the subacute group and 21 knees/42 MRIs (14 females, 7 males) in the chronic group. Subacute patients had a mean age of 59.5 ± 8.8 years and a mean interval of 4.8 ± 2.6 months between MRIs compared with 53.6 ± 11.0 years and 38.2 ± 20.8 months, respectively, for the chronic group. Meniscal extrusion, femoral modified Outerbridge grade, and tibial modified Outerbridge grade worsened between initial and final MRI in both groups (p < 0.05). In both groups, there were no significant differences between initial and final MRIs with regard to the LaPrade classification, insufficiency fracture, or subchondral cysts of the tibia. Progressive meniscus extrusion and medial compartment articular cartilage degeneration were seen in patients with MMPRTs within a year from diagnosis.
Keywords: medial meniscus posterior root tear; meniscus; root tear